The Pain Disability Questionnaire (PDQ): evaluation of its utility for presurgical and 1-year postsurgical physical and psychosocial outcomes for patients undergoing total knee arthroplasty. Issue 4 (July 2016) - Howard, Krista; Gray, Avia; Ramos, Stephen; Ellis, Henry
Abstract : Background: The Pain Disability Questionnaire (PDQ) assesses perception of disability in relation to pain. Past research confirmed the utility of the PDQ to assess treatment outcomes for patients with chronic disabling occupational musculoskeletal disorders. This study evaluates the utility of the PDQ in a sample of patients undergoing total knee arthroplasty (TKA). Methods: One hundred and thirty patients with TKA completed the PDQ, along with physical and psychosocial measures before surgery and at 12-months postsurgically. Patients were classified into three groups based on their total baseline PDQ scores: mild/moderate (0-70), severe (71-100), and extreme (101-150). Analyses determined if the PDQ groups were significantly associated with baseline and 12-month postsurgical physical and psychosocial outcomes. Results: Patients with severe and/or extreme levels of perceived pain disability were more likely to be younger ( P =0.010), Hispanic ( P =0.013), and to have no college education ( P =0.005). Patients in the extreme group were more likely to have major depressive disorder ( P <001), anxiety disorder ( P =0.007) and/or somatization disorder ( P =0.038). Patients in the severe/extreme groups had higher levels of pain, stiffness, and poor function (all P <0.001) before surgery and greater pain and poorer function 12-months after surgery (all P <0.001). Patients in the extreme group had worse physical and mental quality of life scores at baseline and 12-months after surgery (all P <0.003). Baseline PDQ was significantly associated with both the 12-month postsurgical Western Ontario and McMasters Universities Arthritis index (WOMAC) ( P <0.001) and the 12-month postsurgical Short Form-36 (SF-36) mental composite ( P <0.001). Conclusions: The PDQ is a useful presurgical measure for assessing both baseline and postsurgical physical and psychosocial outcomes for patients undergoing TKA. Level of Evidence: Level II, Prospective Cohort Study.